2010
DOI: 10.1159/000313489
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Chemokine Receptors in Renal Inflammation

Abstract: Chemokines are structurally related proteins which form a large family of chemotactic cytokines. They provide a general communication system for cells and regulate lymphocyte migration. These proteins orchestrate the formation of microenvironments in lymphoid tissue, promote lymphoid organogenesis and help foster vascular and lymphatic angiogenesis. In addition to the classical G proteincoupled chemokine receptors, many chemokines also bind to a family of nonsignaling proteins, now called interceptors (chemoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…Consecutives studies have clearly shown that the scavenging of chemokines by these atypical receptors plays an essential role in dampening inflammatory responses and induction of resolution (38). Whether chemokine consumption (i.e., binding-internalization-degradation) by classic "proinflammatory" chemokine receptors that do not belong to the nonsignaling family of scavenger receptors, such as CCR5, may be an additional mechanism for downregulation of the host's immune response is largely unknown (32).…”
Section: Discussionmentioning
confidence: 99%
“…Consecutives studies have clearly shown that the scavenging of chemokines by these atypical receptors plays an essential role in dampening inflammatory responses and induction of resolution (38). Whether chemokine consumption (i.e., binding-internalization-degradation) by classic "proinflammatory" chemokine receptors that do not belong to the nonsignaling family of scavenger receptors, such as CCR5, may be an additional mechanism for downregulation of the host's immune response is largely unknown (32).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins expressed by LECs can directly modulate the local inflammatory milieu. The atypical chemokine receptor D6 takes up chemokines which results in digestion and local chemokine clearance [39,40]. The deletion of this receptor in mice leads to chronic inflammation of the skin [39].…”
Section: Role Of the Lymphatic Vasculature In Inflammationmentioning
confidence: 99%
“…In the chemokine system, a group of special receptors, called atypical chemokine receptors (ACKRs) or chemokine decoy receptors, recognize and bind the ligands without causing any signal transduction as they have the ability to capture the chemokines and to annihilated the signals [1][2]. Recently, three ACKRs, Duffy antigen receptor for chemokines (DARC or ACKR1), D6 (ACKR2) and ChemoCentryx chemokine receptor (CCX-CKR or ACKR4), have been widely concerned on their close associations with the occurrence and metastasis of tumors [3].…”
Section: Introductionmentioning
confidence: 99%